Operetta : a Sourcebook, Volume I - Letellier, Robert Ignatius (Cambridge Scholars Publishing, 2015)
Operetta developed in the second half of the 19th century from the French opéra-comique and the more lighthearted German Singspiel. As the century progressed, the serious concerns of mainstream opera were sustained and intensified, leaving a gap between opéra-comique and vaudeville that necessitated a new type of stage work. Jacques Offenbach, son of a Cologne synagogue cantor, established himself in Paris with his series of opéras-bouffes. The popular success of this individual new form of entertainment light, humorous, satirical and also sentimental led to the emergence of operetta as a sepa.